Maintenance of Type IV Secretion Function During Helicobacter pylori Infection in Mice - Emma C. Skoog (American Society for Microbiology, 2020)
ABSTRACT The Helicobacter pylori type IV secretion system (T4SS) encoded on the cag pathogenicity island (cagPAI) secretes the CagA oncoprotein and other effectors into the gastric epithelium. During murine infection, T4SS function is lost in an immune-dependent manner, typically as a result of in-frame recombination in the middle repeat region of cagY, though single nucleotide polymorphisms (SNPs) in cagY or in other essential genes may also occur. Loss of T4SS function also occurs in gerbils, nonhuman primates, and humans, suggesting that it is biologically relevant and not simply an artifact of the murine model. Here, we sought to identify physiologically relevant conditions under which T4SS function is maintained in the murine model. We found that loss of H. pylori T4SS function in mice was blunted by systemic Salmonella coinfection and completely eliminated by dietary iron restriction. Both have epidemiologic parallels in humans, since H. pylori strains from individuals in developing countries, where iron deficiency and systemic infections are common, are also more often cagPAI+ than strains from developed countries. These results have implications for our fundamental understanding of the cagPAI and also provide experimental tools that permit the study of T4SS function in the murine model. IMPORTANCE The type IV secretion system (T4SS) is the major Helicobacter pylori virulence factor, though its function is lost during murine infection. Loss of function also occurs in gerbils and in humans, suggesting that it is biologically relevant, but the conditions under which T4SS regulation occurs are unknown. Here, we found that systemic coinfection with Salmonella and iron deprivation each promote retention of T4SS function. These results improve our understanding of the cag pathogenicity island (cagPAI) and provide experimental tools that permit the study of T4SS function in the murine model.